Medial temporal lobe atrophy and white matter hyperintensities are associated with mild cognitive deficits in non-disabled elderly people: the LADIS study. Issue 11 (14th October 2005) - van der Flier, W M; van Straaten, E C W; Barkhof, F; Ferro, J M; Pantoni, L; Basile, A M; Inzitari, D; Erkinjuntti, T; Wahlund, L O; Rostrup, E; Schmidt, R; Fazekas, F; et al.
Abstract : Objective: To assess the associations of medial temporal lobe atrophy (MTA) and white matter hyperintensities (WMH) with cognitive function in a large group of independently functioning elderly people. Methods: Data were drawn from the multicentre, multinational leukoaraiosis and disability (LADIS) project which is studying prospectively the role of WMH as an independent predictor of the transition to disability in non-disabled elderly people. In all, 639 participants were enrolled in the LADIS study. For the present analysis, data on 581 subjects were available. Cognitive function was assessed by the mini-mental state examination (MMSE). Visual ratings of WMH and MTA were undertaken on magnetic resonance images (MRI). Results: The presence of either severe WMH or MTA was associated with a modest but non-significant increase in frequency of mild cognitive deficits (severe WMH: odds ratio (OR) = 1.9 (95% confidence interval (CI), 1.0 to 3.7); MTA present: OR = 1.5 (95% CI, 0.8 to 2.8)). However, subjects with the combination of MTA and severe WMH had a more than fourfold increase in frequency of mild cognitive deficits (OR = 4.1 (95% CI, 2.3 to 7.4)). Analysis of variance with post hoc Bonferroni t tests showed that subjects with both MTA and severe WMH performed worse on MMSE than those with either no MRI abnormality or a single MRI abnormality (p<0.05). Conclusions: These results provide further evidence for the combined involvement of both Alzheimer type pathology and vascular pathology in the earliest stages of cognitive decline and suggest an additive effect of WMH and MTA.